Global neurosurgery: Reflections on myelomeningocele in the Zanzibar archipelago (Tanzania) - Luis Moreno-Oliveras; Ruben Rodriguez-Mena; Hadia Nahoda; Pilar Chisbert-Genoves; Mohamed Ali Haji; Jose L. Llacer-Ortega; Jose Piquer-Belloch (World Neurosurgery: X, 2023)
Objective: Our main goal was to describe the general characteristics and demographic data of myelomeningocele (MMC) patients at Mnazi Mmoja Surgical NED Institute (MMSNI) in Zanzibar and to assess the clinical characteristics and medium-term result-impact of the implemented health care measures. Methods: This is a retrospective study on 41 MMC patients treated at the MMSNI in Zanzibar (Tanzania) from September 2016 to September 2018. Patient demographics, prenatal care, clinical and radiographic characteristics, surgical management and nursing care, and clinical outcomes were abstracted. Results: The mean age of the patients was 6.1 ± 4.6 days, and 53.7% were males. A total of 51.2% came from Zanzibar, 39% to Pemba, and 9.8% from mainland Tanzania. Maternal ultrasound checkups revealed hydrocephalus in 18.7% of the cases. 85.4% of the newborns were operated on. Surgical wound infection was the most frequent complication (28.6%). A significantly higher risk of complications was observed in children from Pemba Island (p = 0.046) and those born by vaginal delivery (p = 0.694), particularly infections. During follow-up, 48.57% of the patients presented with infantile hydrocephalus and in the majority of them, a ventriculoperitoneal shunt was inserted. Conclusions: Proper prenatal care with early diagnosis, together with the neurosurgical and nursing standard of care in a specialized institution, are all essential to increase the chances of successful treatment of newborns harboring MMC and is one of the main goals pursued in the MMSNI, as the only referral public health center with locally trained health personnel in Zanzibar archipelago.